Strategi Pemenuhan Kebutuhan Masyarakat terhadap Air Bersih di Kabupaten Bengkalis - Sri Endang Kornita (Universitas Samudra, 2020)
The purpose of regional development is to improve the people's welfare. So in an effort to achieve these objectives community-based development planning is needed, by striving for the communities’ basic needs to be accommodated in a transparent, democratic and accountable manner. This study analyze the strategies and determine the model of clean water supply for the community in Bengkalis Regency. The research analysis uses descriptive qualitative and quantitative and SWOT. The SWOT Analysis shown that the community needs for clean water in Bengkalis Regency could be used SO strategies, namely strategies to achieve policy objectives by utilizing the strengths and potential/opportunities that are owned by cooperation between stakeholders. Whereas the water supply model that is possible for community needs in Bengkalis Regency is through the Piping Network (JP) provided by the local government through PDAM BUMD, non-piping / Non-Piping Networks (BJP) through PAMSIMAS and community self-help.